Ea's duplicity in the Gilgamesh flood story - Worthington, Martin ca. 20./21. Jh. (The ancient word, 2019)
"Interrogating" Babylonian narrative poetry -- "Identifying" puns -- The high concentration of puns in the Gilgameš: flood story -- The lines about the flood hero -- Raining "plenty": ušaznanakkunuši nuh'šam-ma -- The birds: [hi'ib] ishurati -- The fish: puzur nuni -- The harvest: [...] mešrâ eburam-ma -- "Cakes at dawn": ina ser(-)kukki -- "In the evening": ina lilâti -- The "rain of wheat": samût kibati -- Recapitulation -- Issues of textual history -- Meaning and performance -- Outlining the problems -- Does Atra-hasīs "fill in the gaps"? -- Communications between Ea and the flood hero -- Communication between the flood hero and the people of Shuruppak -- Ea's elusiveness -- The enigma of uta-napisti -- Why the "gaps"? -- Ea's duplicity and Babylonian/Assyrian divination -- Beyond cuneiform.